Screening for substance misuse in the dental care setting: findings from a nationally representative survey of dentists. (2nd July 2015) - Parish, Carrigan L.; Pereyra, Margaret R.; Pollack, Harold A.; Cardenas, Gabriel; Castellon, Pedro C.; Abel, Stephen N.; Singer, Richard; Metsch, Lisa R.
Abstract Aims The dental setting is a potentially valuable venue for screening for substance misuse. Therefore, we assessed dentists' inquiry of substance misuse through their patient medical history forms and their agreement with the compatibility of screening as part of the dentists' professional role. Design A nationally representative survey of general dentists using a sampling frame obtained from the American Dental Association Survey Center (November 2010–November 2011). Setting United States of America. Participants A total of 1802 general dentists. Measurements A 38‐item survey instrument assessing the relationship between dentists' practice, knowledge, behaviors and attitudes with their query about substance misuse and their belief that such screening is part of their professional role. Findings Dentists who accepted substance misuse screening as part of their professional role were more likely to query about misuse with their patients (85.8%) compared with those who did not accept such screening as part of their role (68.2%) (P < 0.001). Prior experience and knowledge about substance misuse were the strongest predictors of dentists' inquiry about patient substance use/misuse and acceptance of screening as part of their role in their clinical practice (P < 0.05). Conclusion While more than three‐quarters of US dentists report that they ask their patients about substance misuse, two‐thirds do not agree that such screening is compatible with their professional role.